Leaf To Uplift Mindoro: Rehabilitation And Propagation Of Nipa (Nypa Fruticans Wurmb) In Occidental Mindoro - Cadiao, Leah Veloria; Espiritu, Leticia C. (JPAIR Multidisciplinary Research, 2012)
Nypa fruticans wurmb commonly called nipa is the only palm considered as mangrove. It plays an important role in stabilizing river banks preventing, soil erosion and producing various useful products. In Occidental Mindoro, this species is dwindling and might be considered endangered if not given utmost attention at this point in time. The location of the site was mapped out using GPS coordinates. The assessment of nipa was conducted along Amindan River, Bubog, San Jose, and Occidental Mindoro with a plan table area of 7,800 sq m. Nipa species density shows 379 plants on the right side of the river bank and 414 plants on the left side. The seaward zone has the highest density of 770 plants/ha and middle ward zone of 630 plants/ha. The least dense is the landward zone of 247 plants/ha. A survey questionnaire and unstructured interview were administered and conducted respectively among 30 randomly selected stakeholders. Continuous consultation and partnership with the community and other stakeholders; provision of financial and technical support from collaborating agencies, nursery establishment and additional trainings and seminar to enhance the participation of the community are the most important strategies done in the implementation of the project.